Latent Photoinduced Oxygen Doping Revealed from Emission Saturation of Aggregated Domains in Conjugated Polymer Nanofibers - David J. Walwark Jr.; Thomas P. Martin Jr.; John K. Grey (Advanced Electronic Materials, 2020)
Abstract Photoinduced oxidation (doping) of conjugated polymers by complexation with oxygen can have a significant impact on electronic properties and performance in device environments. Nanofiber model forms of poly(3‐hexylthiophene) (P3HT) are investigated using single molecule spectroscopy that possess similar morphological qualities as their bulk thin film counterparts yet, heterogeneity is confined to the spatial dimensions of these particles. Specifically, P3HT nanofibers assembled in anisole solutions contain both aggregated and nonaggregated (amorphous) chains with distinct electronic properties. Excitation intensity dependent photoluminescence (PL) emission imaging is then used to expose differences in oxygen affinity and reactivity upon photoexcitation. Nanofiber regions with low PL yields tend to show faster PL intensity saturation that also degrade much faster following periods of high excitation intensity soaking. Conversely, other regions show gains in PL intensity and virtually no saturation. These PL “gainer” and “loser” behaviors are assigned as originating from amorphous and aggregated P3HT chains, respectively. The apparent propensity of aggregated chains to undergo latent oxygen doping indicates a greater affinity probably due to a larger extent of electronic delocalization in these structures. The results shed new light on degradation factors studied frequently at the bulk material level, which often lacks sufficient sensitivity to specific structural forms.